Abundance and Characteristics of Microplastics in Coastal Sediment and Seawater Collected from Surabaya and Tulungagung - Indriyasari, Khudrotul Nisa; Rahmatin, Nailul Muthiati; Marchellina, Ary; Mukholladun, Wildanun; Soegianto, Agoes (The Journal of Experimental Life Science, 2024)
This research attempted to determine the abundance and characteristics, including morphology, color, and size of microplastics found in coastal sediment and seawater of Wonorejo, Surabaya, which is located on the north coast of East Java, and Popoh, Tulungagung on the south coast of East Java. Water and sediment samples were collected during the dry season with two replications. The standard method of water sample laboratory preparation and microplastic identification was carried out using NOAA Technical Memorandum NOS-OR&R-48, while the sediment sample was prepared with several modifications. The average microplastic abundance in Surabaya and Tulungagung seawater samples is equal to 2100 particles m-3 and 170 particles m-3, respectively. Meanwhile, as many as 740 particles kg-1 and 350 particles kg-1 were found consecutively in sediment samples of Surabaya and Tulungagung. Microplastics in seawater samples were dominated by 44.7% red and 80.9% fiber, while 43.1% black and 51.4% fiber microplastics were primarily found in sediment samples. The microplastic size ranges from 30—1450 μm in seawater samples and 50—3750 μm in sediment samples. Keywords: abundance, characteristics, microplastics, seawater, sediment.